2016
DOI: 10.3892/etm.2016.3962
|View full text |Cite
|
Sign up to set email alerts
|

Aloperine attenuates hydrogen peroxide-induced injury via anti-apoptotic activity and suppression of the nuclear factor-κB signaling pathway

Abstract: Abstract. Aloperine is an alkaloid that exerts significant inhibitive effects on acute inflammation and Type Ⅲ and Ⅳ hypersensitivity caused by a variety of inflammatory agents. The aims of the present study were to investigate whether the protective effect of aloperine attenuates hydrogen peroxide (H 2 O 2 )-induced injury, and to identify the underlying mechanisms involved. Nucleus pulposus cells were extracted from adult male Sprague-Dawley rats, and incubated with fresh medium containing 200 µM H 2 O 2 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…The results showed that the major indicators of oxidative stress, including ROS, MDA, GST, were increased, while GPX was decreased in RSC96 cells after HG treatment, but this was reversed by aloperine. Thus, in Schwan cells aloperine alleviated oxidative stress induced by HG, which was similar to previous studies [23,25]. Aloperine attenuated alterations in oxidative stress biomarkers induced by monocrotaline in pulmonary hypertensive rats [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that the major indicators of oxidative stress, including ROS, MDA, GST, were increased, while GPX was decreased in RSC96 cells after HG treatment, but this was reversed by aloperine. Thus, in Schwan cells aloperine alleviated oxidative stress induced by HG, which was similar to previous studies [23,25]. Aloperine attenuated alterations in oxidative stress biomarkers induced by monocrotaline in pulmonary hypertensive rats [23].…”
Section: Discussionsupporting
confidence: 89%
“…Aloperine attenuated alterations in oxidative stress biomarkers induced by monocrotaline in pulmonary hypertensive rats [23]. Aloperine also reduced oxidation activity induced by H2O2 [25]. Therefore, these results indicated that aloperine alleviated HG-induced oxidative stress in RSC96 cells.…”
Section: Discussionmentioning
confidence: 70%
“…Aloperine is a quinolizidine alkaloid that has been isolated from S. alopecuroides extract [ 3 ]. It has been reported to possess multiple pharmacological activities, including antimicrobial, antiviral, anti-allergic, anti-renal injury, anti-neuronal injury, anti-inflammatory, antinociceptive, and antitumor effects [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The antitumor effects of aloperine have also been demonstrated on several human cancer cells, including colon cancer, lung cancer, and multiple myeloma [ 2 , 8 , 13 ]; however, there is a lack of studies on its antitumor effects on human thyroid cancers and the associated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits various pharmacological activities, including antibacterial, anti-allergic, antiviral, anti-renal injury, anti-nerve injury, anti-inflammatory, and anti-tumor effects. [14][15][16][17][18] The antitumor effects of ALO have been demonstrated in several human cancer cells, including lung, colon, and multiple myeloma. [18][19][20][21] However, few studies explored its anti-tumor effect on BCs and its related mechanism.…”
Section: Introductionmentioning
confidence: 99%